2018
DOI: 10.1155/2018/4026140
|View full text |Cite
|
Sign up to set email alerts
|

Study on Vibrational Power Flow Propagation Characteristics in a Laminated Composite Cylindrical Shell Filled with Fluid

Abstract: The characteristics of vibrational power flow in an infinite laminated composite cylindrical shell filled with fluid excited by a circumferential line cosine harmonic force are investigated using wave propagation approach. The harmonic motions of the shell and the fluid filled in the shell are described by Love shell theory and acoustic wave equation, respectively. Under the driving force, the vibrational power flow input into the coupled system and the transmission of the power flow carried by different inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They found that the power flow of the sandwich beam reduces with the greater extent of attenuation of the flexural wave. Liu et al [10] studied propagation characteristics of the vibrational power flow in a laminated composite cylindrical shell filled with fluid. At present, the power flow analysis becomes an important tool for studying the structural noise [11], isolation system [12], power transmission [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the power flow of the sandwich beam reduces with the greater extent of attenuation of the flexural wave. Liu et al [10] studied propagation characteristics of the vibrational power flow in a laminated composite cylindrical shell filled with fluid. At present, the power flow analysis becomes an important tool for studying the structural noise [11], isolation system [12], power transmission [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of authors' knowledge, no work had been reported on the vibration power flow analysis of micro-/nano-structures. Liu et al [7] studied the vibrational power flow in a cylindrical shell filled with fluid under a dynamic force loading. Cho et al [8] developed the structural intensity technique to analyze the vibrational energy flow in plates that are under a harmonic excitation.…”
Section: Introductionmentioning
confidence: 99%